Caregiver Burden in Frontotemporal Degeneration and Corticobasal Syndrome - Armstrong, Nicole (Dement Geriatr Cogn Disord, 2013)
BACKGROUND AND AIMS: Caregiver stress is often a serious problem when caring for a patient with frontal lobe dysfunction. METHODS: A total of 102 caregivers of both patients with frontotemporal degeneration and corticobasal syndrome completed the Frontal Systems Behavior Scale (FrSBe) and the Zarit Burden Interview (ZBI). To analyze the association between apathy or disinhibition (or both) and caregiver burden, the effects of the total FrSBe and the apathy and disinhibition subscales of the FrSBE on the total ZBI score were assessed with logistic regressions and t tests. RESULTS: Total FrSBE score and the apathy FrSBE subscore predicted caregiver burden. Apathy occurred without disinhibition, and the two occurred together, but disinhibition without apathy was very rare. CONCLUSIONS: Disinhibition without apathy occurred very rarely. Apathy was more associated with caregiver burden than disinhibition.